Dephosphorylated Polymerase I and Transcript Release Factor Prevents Allergic Asthma Exacerbations by Limiting IL-33 Release - Ni, Yingmeng; Hao, Jimin; Hou, Xiaoxia; Du, Wei; Yu, Youchao; Chen, Tiantian; Wei, Zhuang; Li, Yangyang; Zhu, Fuxiang; Wang, Shuaiwei; Liang, Rui; Li, Dan; et al. (Frontiers in Immunology, 2018)
Background Asthma is a chronic inflammatory disease characterized by airway inflammation and airway hyperresponsiveness (AHR). IL-33 is considered as one of the most critical molecules in asthma pathogenesis. IL-33 is stored in nucleus and passively released during necrosis. But little is known about whether living cells can release IL-33 and how this process is regulated. Objective We sought to investigate the role of polymerase I and transcript release factor (PTRF) in IL-33 release and asthma pathogenesis. Methods Ovalbumin (OVA)-induced asthma model in PTRF+/− mice were employed to dissect the role of PTRF in vivo. Then, further in vitro experiments were carried out to unwind the potential mechanism involved. Results In OVA asthma model with challenge phase, PTRF+/− mice showed a greater airway hyper-reaction, with an intense airway inflammation and more eosinophils in bronchoalveolar lavage fluid (BALF). Consistently, more acute type 2 immune response in lung and a higher IL-33 level in BALF were found in PTRF+/− mice. In OVA asthma model without challenge phase, airway inflammation and local type 2 immune responses were comparable between control mice and PTRF+/− mice. Knockdown of PTRF in 16HBE led to a significantly increased level of IL-33 in cell culture supernatants in response to LPS or HDM. Immunoprecipitation assay clarified Y158 as the major phosphorylation site of PTRF, which was also critical for the interaction of IL-33 and PTRF. Overexpression of dephosphorylated mutant Y158F of PTRF sequestered IL-33 in nucleus together with PTRF and limited IL-33 extracellular secretion. Conclusion Partial loss of PTRF led to a greater AHR and potent type 2 immune responses during challenge phase of asthma model, without influencing the sensitization phase. PTRF phosphorylation status determined subcellular location of PTRF and, therefore, regulated IL-33 release.